From Ratings And Purchase Decisions:Brand Image Perspective - Elfira, Winda; Azhar, Andi (Jurnal Fokus Manajemen, 2024)
The title of this research is Online Ratings to Purchase Dicisions: Brand Image Perspective. The purpose of this research is to determine the influence of Ratings Online Customer Review, Number of Sales, Product Displays on Purchasing Decisions on the Shopee Marketplace with Brand Image as a mediating variable. The research sample used the Shopee Marketplace in big cities in Indonesia, With 132 respondents selected using the Accidental Sampling method. Data was collected through questionnaires and analyzed using Structural Mommet Analysis (AMOS). Software. The results og this research show that user ratings, Online Customer Review, number of sales, product displays have a significant Influence,on brand image and purchasing decisions. However, Brand Image only plays a mediating role in the influence of Ratings , Online Customer Reviews, Number of sales, Product Displays on Purchasing Decisions.